Peningkatan keterampilan menulis narasi melalui model scaffolded writing dengan gambar seri pada siswa kelas iii sekolah dasar - Lestari, Ika Desi; Mulyono, Hadi; Hartono, Hartono (Universitas Sebelas Maret, 2021)
Abstract. The research’s aim is improving the skill of narrative writing the 3th grade students in Jenar Lor Elementary School in 2018/2019. This study’s type is class action research that held in two cycles whoose two meeting in every cycle. The subjects of this study were the teacher and 3th grade students of Jenar Lor Elementary School, amounting to 24 students. The data was collected by test, interview, observation and documentation. The data wa analyse by collecting, presentating, reducting and drawing to the conclusion. The conclusion is by applicating Scaffolded Writing model with serial image media can improve the writing skills of 3th grade students in SDN Jenar Lor in academic year 2018/2019. In addition, the application of the Scaffolded Writing model with serial image media also improve teacher performance in developing learning models and media and encourages students to actively involve the learning activity so the conducive and pleasant learning atmosphere can be created. Keywords: scaffolded writing, drawing series media, narrative writing skills, elementary school